Turkish preservice science teacher educators’ beliefs about the nature of science and conceptualisations of science education - İrez, O. Serhat (My University, 2004)
Today, promoting functional literacy in science is considered as urgent in democratic societies where citizens have a voice in science funding decisions, evaluating policy matters and weighing scientific evidence provided in legal proceedings, and is accepted as one of the main goals of science education. In this sense, teaching and learning about the nature of science (NOS) has been the focus of attention as a primary component of scientific literacy. Educating knowledgeable science teachers with regard to the NOS has been seen as key in this movement and special attention has been paid to science teacher education. Considering the important role of science teacher educators in developing science teachers’ understandings of the NOS, this study explores fifteen Turkish ‘prospective’ science teacher educators’ beliefs about the NOS and conceptualisations of science education in the context of teacher education reform in Turkey. It also addresses the interplay between these two conceptions, i.e. beliefs about the NOS and conceptualisations of science education. A qualitative approach was adopted in the investigation and data was collected through two sets of interviews with the participants. The analysis of data revealed that most of the participants of the study had inadequate conceptions regarding the NOS. The majority of these inadequate conceptions were concentrated under two aspects of the NOS: scientific method and the tentative NOS. The participants’ inadequate conceptions appeared to linked to their own experiences of school science in Turkey and a lack of prior reflection about the NOS. The investigation into the participants’ conceptualisations of science education revealed that the participants conceptualised a range of goals for science education, some of which were consistent with their understandings of the NOS. The investigation also identified four different orientations to the teaching of science amongst the participants: didactic, activity-driven, discovery and, conceptual change. The study revealed a partial relationship between the NOS understanding and orientation to teaching science in the sense that the more informed the individual with regard to the NOS, the stronger the tendency s/ he has toward the conceptual change orientation in science teaching. The study has implications for the pre-service preparation of science teacher educators, teacher education reform and teacher thinking in both practical and policy level.
Keywords: Bilimin Doğası; Fen Bilgisi_Öğrenim ve Öğretim